Implementation CRM (Customer Relationship Management) in Digital Era - Yualinda, Sherli; Lubis, Muharman; Yualinda, Sherla; Fauzan, Ratandi (Yayasan Asmin Intelektual Berkah, 2026)
The rapid advancement of digital technology has transformed the way companies interact with customers, requiring organizations to adapt their Customer Relationship Management (CRM) strategies to remain competitive in a dynamic market environment. Technology provides customers with greater choice and control, encouraging companies to develop more personalized and deeper relationships. Effective CRM implementation is therefore crucial in the digital era to better understand customer needs, enhance communication, and deliver improved customer experiences. However, CRM implementation also encounters several challenges, including resistance to change, difficulties in integrating legacy systems, complex data management, and limited resources. The success of CRM largely depends on a company’s ability to adapt to evolving customer needs and leverage technology to strengthen long-term relationships. By addressing these challenges, companies can achieve a sustainable competitive advantage.